METHODS OF USING NOTATION SOFTWARE IN MUSIC EDUCATION AND PRACTICE - Usmanova Shohista Shavkat qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The integration of digital technologies into music education has significantly transformed traditional teaching and learning methods. Among the most impactful tools are music notation software programs, which enable users to transcribe, edit, and reproduce musical compositions efficiently. This article explores the methods of using notation software in both educational and creative contexts, analyzing its pedagogical advantages, technical requirements, and practical strategies for effective use. It also examines the role of software like Sibelius, Finale, MuseScore, and Dorico in improving music literacy, facilitating composition, and enhancing students’ engagement with musical material.